Chapter Il lavoro nelle corporazioni nell’Europa del Medioevo: tra identità di gruppo e ordine sociale - Ammannati, Francesco (Firenze University Press, 2025)
While medieval guilds failed to absorb and encapsulate the entire world of labour into their fold, the moral, civic and political impact in medieval societies and the role in articulating rank in an increasingly hierarchical society is unquestionable. Guildsmen believed that their associations promoted 'justice' and that decisions within the guild should express the will of the majority of peers. However, this moral ethic, this concept of brotherhood, led to the exclusion from the world of production and, by extension, civil society, of all those who were outside the guild system. This system limited the resourcefulness of some and entailed the survival of the mediocre, but it was an acceptable compromise to ensure the security, order and reliability of the economic and social system for the majority.